Hemorrhagic Cystitis Secondary to Adenovirus and BK Virus Infection in a Diffuse Large B-Cell Lymphoma Patient with Recent CAR T-Cell Therapy - Khan, Abdul Moiz; Ajmal, Zainub; Tuz Zahra, Fatima; Ramani, Ananthakrishnan; Zackon, Ira (Case Reports in Hematology, 2020)
Patients who undergo chimeric antigen receptor T-cell therapy (CAR T-cell therapy) are immunosuppressed due to multiple factors. While adenovirus and BK virus are well-known pathogens in the context of hematopoietic stem cell transplant, there are no detailed reports of these infections in the setting of CAR T-cell therapy. We describe a 70-year-old male who recently underwent CAR T-cell therapy for diffuse large B-cell lymphoma. He presented with intractable gross hematuria and dysuria. Workup revealed adenovirus viremia and viruria and BK virus viruria. He was treated for adenovirus hemorrhagic cystitis with intravenous cidofovir 1 mg/kg/day, every three days for three weeks, with good clinical response. We also discuss the mechanisms of immunosuppression in CAR T-cell therapy as well as the principles of treatment of adenovirus and BK virus infections in the immunosuppressed patient.